Kakigori summer = [Kakigori no natsu] - Itami, Emily (Mariner Books, 2025)
When music idol Ai is embroiled in scandal, her sisters, ambitious Rei and single mother Kiki, pause their lives and spend the summer with Ai in their childhood home on the Japanese coast so they can rescue their baby sister.